2019
DOI: 10.1590/s1678-9946201961034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular typing of rotavirus in children with acute diarrhoea in Northeastern Colombia

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…We believe that the emergence of Wa-1 equine-like G3P [8] in this study may be the result of a rearrangement between a non-previously reported equine-like-DS-1 variants and a local Wa-like strain as has been reported elsewhere [29]. Since G12P [8] strains have been recently reported in Colombia [6], it could be possible that backbone strains belong to local G12P [8] with a high identity (>99.4%) to human G12P [8] strains from Spain (Table 1).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…We believe that the emergence of Wa-1 equine-like G3P [8] in this study may be the result of a rearrangement between a non-previously reported equine-like-DS-1 variants and a local Wa-like strain as has been reported elsewhere [29]. Since G12P [8] strains have been recently reported in Colombia [6], it could be possible that backbone strains belong to local G12P [8] with a high identity (>99.4%) to human G12P [8] strains from Spain (Table 1).…”
Section: Discussionsupporting
confidence: 67%
“…A recently published case-control study assessing the etiology of moderate to severe acute gastroenteritis in children that were less than 5 years of age, carried out in the same city from the patient of our current study (Bucaramanga, Colombia), found that norovirus and rotavirus explained the major proportion of moderate to severe clinical cases [35]. However, after the introduction of RVA vaccination in 2009, there was a reduction of 39% in diarrhea-related mortality in children <5 years old (95% CI, 35 to 44) in Colombia [36], with a rapid switch from Wa-like to DS-1-like strains [37] and a high frequency of unusual G9P [4] in 2012 [38] and G3 P[8]/P [9] strains accounting for the vast majority of cases (82.8%) in 2015-2016 [6]. As has been seen in other countries in Latin America, the strong bias towards G3 strains, mainly in Brazil, is mostly due to the presence of the Equine-like RVA strains [12,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7–10 Others found no sex differences in incidence. 11 , 12 Rotaviral enteritis among adults has not decreased despite effective vaccination in childhood; infections with rotavirus among adults are generally underappreciated by age and sex 13 , 14 and may spread between patients, making recognition of rotaviral enteritis important for infection control. 15–17 …”
Section: Introductionmentioning
confidence: 99%